Assumptions and Formation of the Aesopian Language in the Soviet Lithuania - Klumbys, Valdemaras (Genocidas ir rezistencija, 2016)
The article analyses the genesis of the Aesopian language in Lithuania. The rudiments of the Aesopian language existed prior to the Soviet occupation, but there were no established traditions for the creation and use of such language. This gives rise to the question how the Aesopian language with its coherent code system, which was more or less understood by totally unrelated people, could have been created and spread in the repressive Soviet system. The study has shown that it was the Soviet regime that not only created premises and conditions conducive to the Aesopian language, but actually taught the grammar and lexis of this language.First, the Stalin regime taught to treat people, actions and texts with suspicion. The regime taught this both directly through the pursuit of enemies of the regime and wide-spread suspicion, and indirectly – through the fear of reprisals and distrust among people. Second, the regime strongly politicised all texts and actions. It is also important that politisation was achieved through reinterpretation of the texts or actions. As a result, a habit and skill to easily change meanings was instilled, which is an important mechanism of the Aesopian language. Third, by disclosing enemies and the inconsistencies between the texts and the prevailing ideological discourse, the regime also taught people specific codes by indicating what the regime found unacceptable and how specifically this was encoded and expressed.The Aesopian language came into operation when the public took over all these characteristics implemented by the regime. Several stages in the functioning of the Aesopian language could be identified. Initially, the interpretative clichés implemented by the regime were used, except that the assessment was exactly the opposite to the official assessment. Subsequently, the mechanisms implemented by the regime were used creatively and new Aesopian codes were created.It took about two decades (1940s–1950s) to learn the Aesopian language, although examples of its individual use can be found at the very beginning of the Soviet occupation. However, the Aesopian language could spread widely and become systematic only after the in-depth Sovietisation of the Lithuanian society, when Lithuania became fully immersed in the Soviet culture and took over Soviet practices. Therefore, the use of the Aesopian language meant further and deeper reproduction of the Soviet culture despite that the language sought to criticise the regime.
Keywords: Lithuania; Soviet regime; censorship; literature